Identification and mapping of two divergent, unlinked major histocompatibility complex class II B genes in Xiphophorus fishes. - McConnell, Thomas J.; Godwin, Ulla B.; Norton, Stephen F.; Nairn, Rodney S.; Kazianis, Steven; Morizot, Donald C. (East Carolina University, 1998)
We have isolated two major histocompatibility complex (MHC) class II B genes from the inbred fish strain Xiphophorus maculatus Jp 163 A. We mapped one of these genes, designated here as DXB, to linkage group III, linked to a malic enzyme locus, also syntenic with human and mouse MHC. Comparison of genomic and cDNA clones shows the gene consists of six exons and five introns. The encoded b1 domain has three amino acids deleted and a cytoplasmic tail nine amino acids longer than in other teleost class II b chains, more similar to HLA-DRB, clawed frog Xela-F3, and nurse shark Gici-B. Key residues for disulfide bonds, glycosylation, and interaction with a chains are conserved. These same features are also present in a swordtail (Xiphophorus helleri) genomic DXB PCR clone. A second type of class II B clone was amplified by PCR from X. maculatus and found to be orthologous to class II genes identified in other fishes. This DAB-like gene is 63% identical to the X. maculatus DXB sequence in the conserved b2-encoding exon and was mapped to new unassigned linkage group LG U24. The DXB gene, then, represents an unlinked duplicated locus not previously identified in teleosts. Originally published Genetics Vol. 149, No. 4, August 1998
Keywords: Xiphophorus fishes; Histocompatibility complex; Gene mapping